STUDI DAMPAK USAHA PENGGILINGAN BATU TERHADAP KONDISI MASYARAKAT DI DESA WATUKALANGKARI KECAMATAN RUMBIA KABUPATEN BOMBANA - Wantari, Winda (JIDE : Journal Of International Development Economics, 2022)
To purpose of this study is to find out the impact of the stone grinding business on the condition of the people in Watukalangkari . The data used are primary data and secondary data. Data obtained by observation, interview, and documentation. This research use descriptive qualitative and quantitative method. The results of the research indicate that the income of the income of the respondents' economy increased, namely before the existence of the stone grinding company PT. Merah Putih Alam Lestari the average income of respondents is Rp. 1,026,087 per month and after the existence of a stone grinding company PT. Merah Putih Alam Lestari the level of income of respondents rose to Rp. 2,239,130 ??per month. The socio-economic conditions of the workers in the stone grinding machine industry in Watukalangkari Village are mostly middle school-educated parents, the status of the house is self-owned, with income between Rp. 750,000 - Rp. 1,000,000, expenses for school are more than Rp. 250,000 per month and without side work.